TAFSIR MAQASID DALAM MEMAHAMI AYAT-AYAT HUKUM: ANALISIS TAFSIR AL-JASSAS - Saleh, Muhammad; Riyadi, Abdul Kadir; Mubarok, Nafi' (Living Islam: Journal of Islamic Discourses, 2024)
Maqasid interpretation, or interpretation based on the goals of Islamic law, plays an important role in deepening the understanding of Qur'anic legal verses. It seeks to uncover the intentions and purposes hidden behind the legal verses, highlighting the legal aspects underlying the rules. One of the tafsir works that considers this approach is Tafsir al-Jassas. This article analyses the contribution of Tafsir al-Jassas in revealing the maqasid (objectives) of Islamic law, especially in the context of legal verses. The content analysis method is used to explore al-Jassas' views on selected legal verses, focusing on the interpretations and interpretations he produces. The findings of this analysis illustrate how al-Jassas' commentaries provide deep insights into the application of maqasid in Islamic law, demonstrating its relevance in the modern legal context. The conclusion of this article emphasises the importance of expanding the use of maqasid-based interpretive approaches in understanding the Islamic legal heritage, to address contemporary challenges and enhance a more holistic understanding of the values and objectives of shari'a law. Keywords: Verses of Law, Tafsir Al-Jassas   Tafsir maqasid, atau penafsiran berdasarkan tujuan-tujuan syariat Islam, memainkan peran penting dalam memperdalam pemahaman terhadap ayat-ayat hukum Al-Qur'an. Tafsir ini berusaha mengungkap maksud dan tujuan yang tersembunyi di balik ayat-ayat hukum, menyoroti aspek-aspek hukum yang mendasari aturan-aturan tersebut. Salah satu karya tafsir yang mempertimbangkan pendekatan ini adalah Tafsir al-Jassas. Artikel ini menganalisis kontribusi tafsir al-Jassas dalam mengungkapkan maqasid (tujuan-tujuan) hukum Islam, khususnya dalam konteks ayat-ayat hukum. Metode analisis konten digunakan untuk mengeksplorasi pandangan al-Jassas terhadap ayat-ayat hukum yang dipilih, dengan fokus pada interpretasi dan penafsiran yang dihasilkannya. Temuan dari analisis ini menggambarkan bagaimana tafsir al-Jassas memberikan wawasan mendalam mengenai aplikasi maqasid dalam hukum Islam, menunjukkan relevansinya dalam konteks hukum modern. Kesimpulan artikel ini menekankan pentingnya memperluas penggunaan pendekatan tafsir berbasis maqasid dalam memahami warisan hukum Islam, untuk mengatasi tantangan kontemporer dan meningkatkan pemahaman yang lebih holistik terhadap nilai-nilai dan tujuan hukum syariat. Kata kunci : Tafsir, Ayat-Ayat Hukum, Tafsir Al-Jassas